Design, Synthesis, Pharmacological Screening And Molecular Docking Of Biphenyl Analogues As Anti-Inflammatory Agents (Part-I) - UJASHKUMAR A. SHAH; NILESH K. WAGH; HEMANTKUMAR S. DEOKAR; SHIVAJIRAO S. KADAM; VITHAL M. KULKARNI (International Journal of Pharma and Bio Sciences, 2010)
Various direct analogues of flurbriprofen [ 4’-methylbiphenyl-2-(substituted phenyl) carboxamide derivatives ] were synthesized and evaluated for anti-inflammatory activity by carrageenan induced rat paw edema model. Compounds 3g, 3h and 3i were found significantly active. Substituents –SO2NH2, -F and -Cl exhibited significant anti-inflammatory activity. Molecular docking was performed using Glide to study the binding mode of these direct analogues of flurbriprofen. The docking analysis of highest active molecule 3g (Glide XP score -8.39) shows significant interaction with active site amino acid residues. Results of this study indicated that these direct analogues of flurbriprofen have affinity towards COX-2 active site which can further be explored as selective COX-2 inhibitors.